PERAN WALI KELAS DALAM MEMANAJEMEN PESERTA DIDIK KELAS XII DI MAN 1 NGAWI: PERAN WALI KELAS - Siti Fatmah Fatmah; Zuhriana Widya Rahayuningtyas (Institut Agama Islam Ngawi, 2025)
The purpose of this research is to find out the role of the class theacer in the management of class XII MAN 1 NGAWI. The method used is qualitative research using descriptive methods, then data collection in the form of interviews and observation. The role of the homeroom teacher is verry important in supporting the success of students. To create a positive learning environment, it is necessary to take a deep approach to students, so thet the homeroom teacher and students are open to each other so thet it is easy to control, guide and motivate students to continue to develop smoothly both in the social, character, academic, and non academic fields of students. Students have a verry important role in educational institutions as objects in the implementation of education, therefore educational institutions, especially homeroom teachers, need to think about effective and efficient management of students.